Racismo e saúde: um olhar a partir da literatura científica - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Racism and its harmful effects on health have long been a significant problem in societies around the world, where discrimination and systemic inequalities faced by racial and ethnic minorities have profound implications for their general well-being. With this in mind, the general aim of this study is to identify in the literature the evidence or possible occurrences of prejudice and racial discrimination in the care of users of the Unified Health System (SUS). The methodology adopted consists of an Integrative Literature Review, the purpose of which was to provide a synthesis of knowledge on the subject of racial prejudice in the care of users in the SUS, problematizing the issue, based on the collection of data from articles that have already been published, and that present scientific rigor in the information. In this way, the main results show that there are indices of racism in the health services and they are presented through racist behaviors and actions towards users during care. In addition, the study revealed that the theme of racism and health is quite broad and involves fields that go beyond the limits of health, requiring attention and a more critical look at the cause.
Keywords: Racismo; Minorias Étnicas e Raciais; Serviços de Saúde; CNPQ:: CIÊNCIAS DA SAÚDE